The Hollow Ones - Toro, Guillermo Del, 1964-; Hogan, Chuck (New York : Grand Central Publishing, 2020)
Forced to shoot her suddenly violent partner, rookie FBI agent Odessa Hardwicke witnesses the escape of a shadowy form from the deceased agents body, and embarks on a sanity-risking investigation into a centuries-old being.
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees; Fiction; Policewomen -- New Jersey; Newark; Fiction; Justifiable homicide -- Fiction; Murder -- Investigation; Fiction; Occult crime -- Fiction; Paranormal fiction; Horror fiction; Thrillers (Fiction)